A new, highly aggressive race of Austropuccinia psidii infects a widely planted, myrtle rust- resistant, eucalypt genotype in Brazil - Almeida, Rosiane Fátima de (2021)
Myrtle rust (MR) caused by Austropuccinia psidii is one of the most important diseases affecting eucalypt (Eucalyptus spp.) plantations in Brazil. Over the years, selection and planting of MR-resistant clones has been the primary strategy for MR management. In May 2013, young trees of the GG100 hybrid (E. grandis  E. urophylla) clone – widely planted in Brazil and previously classified as resistant to MR – were infected by A. psidii in Minas Gerais, Brazil. In this study, artificial inoculations of a eucalypt clone set with differential reactions to A. psidii races were used to discover a new race of A. psidii (race 5) that was highly aggressive on the majority of eucalypt clones tested. In addition, only this new race successfully infected eucalypt 847 genotype, which was formerly classified as resistant to the four previously known races of A. psidii. Our findings demonstrate that this new A. psidii race is highly aggressive and capable of infecting a larger number of eucalypt genotypes compared to the previously known A. psidii races 1, 2, 3, and 4. Keywords: Puccinia psidii. Physiological variability. Eucalyptus.